Interfacial Adhesion and Damping Characteristics of Laminated Veneer Lumber Intercalated with Rubber Sheets - Jingquan Han; Jining Lv; Xianxu Zhan; Runzhou Huang; Xinwu Xu (BioResources, 2016)
Laminated wood veneer lumber intercalated with rubber sheets (LLVR) was fabricated using a layered adhesive system composed of polyaryl polymethylene isocyanate (PAPI) for wood-rubber inter-bonding and phenol formaldehyde (PF) resin to glue the wood veneers. The optimized manufacturing process (chloroprene rubber: CR; PAPI: 80 g/m2; PF: 200 g/m2; and silane: 9.0 wt.%) was determined. The process as developed was then utilized to fabricate nine-ply LLVRs of five balanced constructions with two or three CR laminates used as various layers. The physico-mechanical properties of the LLVRs were evaluated, and the results showed that LLVRs had strong shear strength, sound dimensional stability, decent bending strength, and favorable toughening and buffering performances. The newly developed product is an interesting potential alternative to traditional laminated veneer lumber or plywood.